Can shifts in metabolic scaling predict coevolution between diet quality and body size - Pequeno, Pedro A C L; Graça, Márlon B; Oliveira, João R; Šobotník, Jan; Acioli, Agno N S (Evolution, 2021)
Larger species tend to feed on abundant resources, which nonetheless have lower quality or degradability, the so-called Jarman-Bell principle. The "eat more" hypothesis posits that larger animals compensate for lower quality diets through higher consumption rates. If so, evolutionary shifts in metabolic scaling should affect the scope for this compensation, but whether this has happened is unknown. Here, we investigated this issue using termites, major tropical detritivores that feed along a humification gradient ranging from dead plant tissue to mineral soil. Metabolic scaling is shallower in termites with pounding mandibles adapted to soil-like substrates than in termites with grinding mandibles adapted to fibrous plant tissue. Accordingly, we predicted that only larger species of the former group should have more humified, lower quality diets, given their higher scope to compensate for such a diet. Using literature data on 65 termite species, we show that diet humification does increase with body size in termites with pounding mandibles, but is weakly related to size in termites with grinding mandibles. Our findings suggest that evolution of metabolic scaling may shape the strength of the Jarman-Bell principle.
Keywords: Isoptera; Animals; velikost těla; dieta; mandibula; zvířata; biologická evoluce; Biological Evolution; Body Size; Diet; Mandible